2022
DOI: 10.9734/ijecc/2022/v12i930748
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Analysis for Yield and Its Contributing Traits in Rice Germplasm (Oryza sativa L.) Using Principal Component Analysis Approach

Abstract: The present study was aimed to assess genetic variation among rice germplasm lines employing a multivariate biometrical approach, viz., Principal Component Analysis.  Analysis of variance as per Augmented Block Design indicated the presence of sufficient genetic variation among rice germplasm lines, while estimates of components of variation revealed a maximum contribution of genotypic variance to the phenotypic variance, suggesting its exploitation through selection and hybridization. Simultaneously, correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
3
0
0
Order By: Relevance
“…Analysis of variance (Table 1) as per augmented block design revealed significant differences among the lines for all traits recorded indicating enormous amount of differences among the lines thereby, hinting sufficient scope of selection among the lines followed by hybridization. These results are in close agreement with the results of Devi et al [8] and Choudhary et al [9] in their respective research studies. Genetic components of variation estimated (Table 2) revealed that phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV), thereby, indicating that environment has played mega role in the infestation of these traits.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Analysis of variance (Table 1) as per augmented block design revealed significant differences among the lines for all traits recorded indicating enormous amount of differences among the lines thereby, hinting sufficient scope of selection among the lines followed by hybridization. These results are in close agreement with the results of Devi et al [8] and Choudhary et al [9] in their respective research studies. Genetic components of variation estimated (Table 2) revealed that phenotypic coefficient of variation (PCV) was higher than genotypic coefficient of variation (GCV), thereby, indicating that environment has played mega role in the infestation of these traits.…”
Section: Resultssupporting
confidence: 93%
“…Days to 50 per cent flowering, days to maturity and panicle length were found to have moderate values of PCV and GCV suggesting that these can be improved through positive selection based on phenotypic variation. Results of present study are in agreement with the results of Kumar et al [10] and Choudhary et al [9]. Components of variation calculated through PCV and GCV delineates limit of genetic differences in a plant population but provide no information related to genetic and environmental factors affecting selection pressure therefore, heritability estimates depicts proportion of total variation which can be inherited from generation to generation and guides breeders to develop efficient and goal oriented breeding programme.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation